Delayed wound healing and postoperative surgical site infections in patients with rheumatoid arthritis treated with or without biological disease-modifying antirheumatic drugs. Issue 6 (June 2016) - Tada, Masahiro; Inui, Kentaro; Sugioka, Yuko; Mamoto, Kenji; Okano, Tadashi; Kinoshita, Takuya; Hidaka, Noriaki; Koike, Tatsuya
Abstract Biological disease-modifying antirheumatic drugs (bDMARDs) have become more popular for treating rheumatoid arthritis (RA). Whether or not bDMARDs increase the postoperative risk of surgical site infection (SSI) has remained controversial. We aimed to clarify the effects of bDMARDs on the outcomes of elective orthopedic surgery. We used multivariate logistic regression analysis to analyze risk factors for SSI and delayed wound healing among 227 patients with RA (mean age, 65.0 years; disease duration, 16.9 years) after 332 elective orthopedic surgeries. We also attempted to evaluate the effects of individual medications on infection. Rates of bDMARD and conventional synthetic DMARD (csDMARD) administration were 30.4 and 91.0 %, respectively. Risk factors for SSI were advanced age (odds ratio [OR], 1.11;P = 0.045), prolonged surgery (OR, 1.02;P = 0.03), and preoperative white blood cell count >10, 000/μL (OR, 3.66;P = 0.003). Those for delayed wound healing were advanced age (OR, 1.16;P = 0.001), prolonged surgery (OR, 1.02;P = 0.007), preoperative white blood cell count >10, 000/μL (OR, 4.56;P = 0.02), and foot surgery (OR, 6.60;P = 0.001). Risk factors for SSI and medications did not significantly differ. No DMARDs were risk factors for any outcome examined. Biological DMARDs were not risk factors for postoperative SSI. Foot surgery was a risk factor for delayed wound healing.